Reshaping the International Monetary Architecture : Lessons from Keynes’ Plan - Piffaretti, Nadia F. (2012)
As the global economy undergoes profound changes, it is becoming apparent that the so-called "Revived Bretton Woods System" has increased the overall vulnerability of the global financial architecture. Therefore, it is worth revisiting the origins of the Bretton Woods conference, and pointing out the relevance for today s framework of Keynes original 1942 plan for an International Clearing Union. This note explores the main characteristics of Keynes' original plan, by revisiting his original writings between 1940 and 1944, and outlining its relevance to the current debate on the international financial architecture. The note suggests that reforms of the international financial architecture should include anchoring the international monetary system on sounder institutional ground.